Jenis dan Jumlah Sedimen Urine Menggunakan Variasi Konsentrasi Pengawet Formalin - Desak Made Sri Maharani; Nurul Inayati; Maruni Wiwin Dinarti (Quality : Jurnal Kesehatan, 2017)
Abstract One of the laboratory tests that can be used to diagnose diseases, especially those related to kidney physiology and abnormalities of the body's metabolism, namely urinalysis. Urine sediments are insoluble elements in urine that come from blood, kidneys and urinary tract such as erythrocytes, leukocytes, epithelial cells, thorax, bacteria, crystals, fungi and parasites. Formalin which is commonly used as a urine preservative is 40% formalin, specifically used to preserve urine sediment is very important if you want to conduct a quantitative assessment of the elements in the sediment. However, the formalin in the market only has a formalin with a concentration of 37% so that the concentration of formalin preservatives needs to be lowered. The purpose of this study was to determine the effect of variations in the concentration of formaldehyde use on the amount and type of urine sediments. different for checking organic and inorganic elements. For the type of urine sediment analyzed descriptively while for the amount analyzed using the One Way Annova test. The results showed variations in the concentration of formalin preservatives 37%, 30%, 20% and 10% did not affect the type and amount of urine sediment. The conclusion of this study is that variations in the concentration of formalin preservatives do not affect the type and amount of urine sediment. Keywords : Formalin,Quantity and type, Sedimen Urine